The Green Road - Enright, Anne, 1962- (London Vintage, 2016)
Rosaleen is matriarch of the Madigans, a family on the cusp of either coming together or falling irreparably apart. As they grew up, Rosaleen's four children left the west of Ireland for lives they could have never imagined in Dublin, New York, and Mali, West Africa. In her early old age their difficult, wonderful mother announces that she's decided to sell the house and divide the proceeds. Her adult children come back for a last Christmas, with the feeling that their childhoods are being erased, their personal history bought and sold.
Keywords: Ireland -- Families -- Interpersonal relations